Memanusiakan Pahlawan Devisa: Pemberdayaan dan Advokasi Komunitas Migran Indonesia di Malaysia - Suhada, Suhada; Idries, Fahmy Akbar; Nasrulloh, Rifqi Syarif; Wulandari, Novi Diah (Rahmatan Lil 'Alamin Journal of Community Services, 2024)
This study addresses the challenges and needs of Indonesian migrant workers in Malaysia, who encounter issues such as poor living conditions, limited healthcare access, inadequate education, and insufficient legal protection. Wage disparities and job availability in Indonesia drive migration to neighboring countries, but a lack of skills often results in serious problems like job mismatches, human trafficking, and illegal labor. The aim of this community services is to identify the initial needs for developing the Indonesian international migrant community in Malaysia, with synergy between Indonesian universities and international students in Malaysia. The study employs a qualitative approach through interviews and Focus Group Discussions (FGD) with migrant workers. Findings indicate that many migrants live in inadequate housing with limited access to clean water and sanitation. They also face significant barriers to accessing healthcare, education for their children, and legal protection. Recommendations include improving housing conditions, enhancing healthcare access, providing formal education for migrant children, ensuring legal protection, and promoting economic empowerment through entrepreneurship and financial management training. Effective development and improved welfare for migrants require collaboration between the government, NGOs, universities, and local communities.